Tecnologias educativas e entrevista motivacional breve para promoção da autoeficácia materna na prevenção da diarreia infantil - Mendes, Elizamar Regina da Rocha (2018)
Educational strategies based on self-efficacy may contribute to an increase in maternal self-efficacy in preventing childhood diarrhea. In this sense, the objective of the study was to analyze the educational technologies, video and booklet, associated with the Brief Motivational Interview (BME) in maternal self-efficacy for the prevention of childhood diarrhea. Experimental study Randomized clinical trial with two groups: video plus EMB and primer plus EMB. Performed in two Units of Primary Health Care (UAPS) of Regional V, Fortaleza / CE. The population was composed of mothers of children under 5 years of age and the sample, of 122 of these. The Maternal Self-Efficacy Scale for Childhood Diarrhea Prevention (EAPDI), the socioeconomic form and the reduced form of diarrhea investigation were used. The data collection took place in three phases: in the first phase, in the unit itself, the EAPDI and the form were applied, in the second phase, the interventions, then the scale was applied in the UAPS and in the 3rd phase, the follow-up by telephone contact, with the scale and diarrhea investigation form, for two months. The CRs and their 95% CI were calculated. Analyzes of the contrasted groups were performed, comparing the efficacy between chi-square, likelihood ratio, Student's t test, Mann-Whitney test and logistic regression (for variables that presented p <0.20 in the analysis bivariate). There was an increase in the means of self-efficacy scores in both groups in the first and second month after the interventions. In the video and EMB group (117.4) points and in the primer group and EMB (116.9) points, having an increase of 7 points, and 4.9 points, respectively. It was observed, therefore, that there was a significant increase in the EAPDI scores in the video and EMB group in relation to the primer and EMB group. It was observed that before the intervention, only 39.3% of the mothers presented high self-efficacy in the video and EMB group, and in the primer and EMB group, the results were similar, less than half of the mothers (42.6%) presented self-efficacy. After the educational intervention, in the first month the video and EMB group increased to 78.4%, and in the second month to 74.5%. In the primer and EMB group, the results were similar, in the first month 83% of the mothers presented high self efficacy and in the second month, 77.8%. Regarding the occurrence of diarrhea, at baseline, it was observed that more than half of the children in each group had diarrhea (Video group and BMS, 57.6% and Group booklet and BMS, 55.7%). During the two months following interventions in both groups, a decrease in diarrhea cases was identified. In the video and EMB group, there was a considerable reduction in diarrheal episodes, 97.9% of the mothers reported that their children did not have diarrhea. Similarly, it occurred with the group of the primer and EMB, in which, after two months of intervention, 95.5% of the children did not have diarrhea. These data indicate that each of the educational interventions associated with the brief motivational interview was able to produce significant results. When considering the odds ratio of each group, it was observed that, after two months of the educational intervention, in the video and BMS group, children were less likely to have diarrheal episodes compared to the primer and BMS groups. It was concluded that both the video and the primer, associated with the Brief Motivational Interview (BMI), were effective in increasing maternal self-efficacy in preventing infant diarrhea and reducing the occurrence of diarrheal episodes.